A Portrait of Child Poverty in Germany - Miles Corak; Michael Fertig; Marcus Tamm (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2005)
This paper offers a descriptive portrait of income poverty among children in Germany between the early 1980s and 2001, with a focus on developments since unification in 1991. Data from the German Socio-Economic Panel are used to estimate poverty rates, rates of entry to and exit from poverty, and the duration of time spent in and out of poverty. The analysis focuses upon comparisons between East andWest Germany,by family structure, and citizenship status. Child poverty rates have drifted upward since 1991, and have been increasing more than the rates for the overall population since the mid-1990s. In part these changes are due to increasing poverty among children from households headed by non-citizens. Children in single parent households are by all measures at considerable risk of living in poverty. There are also substantial differences in the incidence of child poverty and its dynamics between East and West Germany.
Keywords: I32; J13; I38; 330; Poverty dynamics; poverty duration; immigrant households